Pengaruh Kualitas Fungsi Dan Pemenuhan Bahasa Kasih Keluarga Terhadap Kebahagiaan Remaja - Rini, Rini (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2023)
Family plays an important role on teenagers’ happiness. Teenagers’ happiness can be realized if the family performs its functions optimally and if the teenagers receive the love language that is expected from the family. This research has two objectives, the first is to determine the influence of the quality of family roles on teenagers’ happiness, and the second is to determine the influence of love language on teenagers’ happiness. The respondents of this research were 456 teenagers, using accidental sampling technique. Data was collected via a Google Form which was distributed via WhatsApp, Telegram, Facebook, and email. Data analysis uses linear regression. The results of the research show that the quality of family function has impact on teenagers’ happiness and the fulfilment of family love language has also an impact on teenagers’ happiness. Indicators of psychological function and educational function are the most powerful indicators of teenage happiness. Likewise, indicators of quality time and physical touch are the strongest indicators in shaping teenage happiness.